Robert Nozick's "Philosophical Explanations": Implications in bioethics - Palazzani, Laura (Medicina e Morale, 1990)
This article examines the thought of Robert Nozick (who belongs to the contemporary current in United States known as "public ethics"), referring to the book Philosophical Explanations (1981), in which the author exposes the philophical premises of his public intervention, that is his intervention in the legal and social sphere. The metaphysical theory of "self-refer", the epistemological theory of "track" and the ethical theory of "push" and "pull" tend to the affirmation of subjectivism, which supports moral pluralism and relativism and political libertarism. The article points out the implicit and explicit implications of these theories in bioethics in order to propose the referring to realistic personalism as the authentic foundation for a public intervention taking care of person's integrity.